Fashion with a Foreign Flair: Professional Experiences Abroad Facilitate the Creative Innovations of Organizations - Godart, Frédéric C.; Maddux, William W.; Shipilov, Andrew V.; Galinsky, Adam D. (Academy of Management Journal, 2015)
This research explores whether the foreign professional experiences of influential execu-tives predict firm-level creative output. We introduce a new theoretical model, the foreign experience model of creative innovations, to explain how three dimensions of executives’ foreign work experiences—breadth, depth, and cultural distance—predict an organiza-tion’s “creative innovations, ” which we define as the extent to which final, implemented products or services are novel and useful from the standpoint of external audiences. We examined 11 years (21 seasons) of fashion collections of theworld’s top fashion houses and found that the foreign professional experiences of creative directors predicted the creativ-ity ratings of their collections. The results revealed individual curvilinear effects for all three dimensions: moderate levels of breadth and cultural distance were associated with the highest levels of creative innovations, whereas depth showed a decreasing positive effect that never turned negative. A significant three-way interaction shows that depth is the most critical dimension for achieving creative innovations, with breadth and cultural distance important at low but not high levels of depth. Our results show how and why leaders ’ foreign professional experiences can be a critical catalyst for creativity and